129k views
0 votes
Solve, then write, each equation in slope intercept form. ​

Solve, then write, each equation in slope intercept form. ​-example-1

1 Answer

2 votes

Answer:

1) (3,5)

2) (4,-7)

3) (6,4)

4) (-4,-3)

Explanation:

1)

Subtract y from both sides of the equation.

x = 8 − y

x − y = −2

Replace all occurrences of x in x − y = −2 with 8 − y.

x = 8 − y

(8 − y) − y = −2

Subtract y from −y.

x = 8 − y

8 − 2y = −2

Solve for y in the second equation.

x = 8 − y

y = 5

Replace all occurrences of y in x = 8 − y with 5.

x = 8 −(5)

y = 5

Simplify 8 −(5).

x = 3

y = 5

Slope = (3,5)

2)

Multiply each term by 2 and simplify.

2x+y=12

y+6=−x−4

Move all terms containing variables to the left side of the equation.

2x+y=1x+2

y+6=−4

Move all terms not containing a variable to the right side of the equation.

2x+y=1x+2

y=−10

Multiply each equation by the value that makes the coefficients of x opposite.

2x+y=1(−2)⋅

(x+2y)=(−2)(−10)

Simplify.

2x+y=1−2x−4

y=20

Add the two equations together to eliminate x from the system.

2x+y=1+−2x−4

y=20−3

y=21

Divide each term by −3 and simplify.

y = −7

Substitute the value found for y into one of the original equations, then solve for x.

x = 4

slope (4,-7)

3)

Subtract y from both sides of the equation.

2x−y=8x−y=2

Multiply each equation by the value that makes the coefficients of y opposite

2x−y=8(−1)⋅

(x−y)=(−1)(2)

Simplify. 2x−y=8

−x+y=−2

Add the two equations together to eliminate y from the system.

2x−y=8 + −x+y=−2x=6

Substitute the value found for x into one of the original equations, then solve for y.

y=4

slope (6,4)

4)

Simplify 2(x+1).

y−3=2x+2

y=−3(x+5)

Simplify −3(x+5)

y−3=2x+2

y=−3x−15

Move all terms containing variables to the left side of the equation.

−2x+y−3=2

y=−3x−15

Add 3x to both sides of the equation.

−2x+y−3=2

y+3x=−15

Move all terms not containing a variable to the right side of the equation.

−2x+y=5

y+3x=−15

Reorder the polynomial.

−2x+y=5

3x + y=−15

Multiply each equation by the value that makes the coefficients of y opposite.

−2x+y=5(−1)⋅

(3x+y)=(−1)(−15)

Simplify.

−2x+y=5

−3x−y=15

Add the two equations together to eliminate y from the system.

−2x+y=5 + −3x−y=15−5x=20

Divide each term by −5 and simplify.

x=−4

Substitute the value found for x into one of the original equations, then solve for y.

y=−3

slope (-4,-3)

Solve, then write, each equation in slope intercept form. ​-example-1
Solve, then write, each equation in slope intercept form. ​-example-2
Solve, then write, each equation in slope intercept form. ​-example-3
Solve, then write, each equation in slope intercept form. ​-example-4
User Marioosh
by
5.8k points